Assessing key physical properties of the Rotorua, Kaharoa and Taupō tephras for their potential use in hydroponics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Earth Science at Massey University, Manawatū, New Zealand - McLachlan, Susan (Massey University, 2024)
Food security is an increasing concern as global populations grow and fertile land availability decreases. Hydroponics, where plants are grown in a soilless medium or nutrient solution, is a potential method of securing food supplies. Understanding the physical and chemical properties of growth media is important as they influence plant growth and productivity. Pumice, a vesicular lightweight material produced by volcanic eruptions, is used in some areas as a growth medium due to its ability to support plant growth. This natural resource is abundant in New Zealand but currently underutilised. The Taupō and Okataina Volcanic Centres (TVC and OVC) in the Central North Island have produced vast volumes of pyroclastic material in the last >60,000 years. This study focused on some of their youngest eruptives, the Kaharoa (OVC), Rotorua (OVC) and Taupō Y (TVC) tephras, to assess their suitability as hydroponic growth media. Samples of the Kaharoa, Rotorua, Taupō Y2 and Y5 deposits and the commercially available Daltons pumice were characterised for grain size then split into hydroponic grades of 1-4 mm and 4-8 mm. The physical properties were used to define relationships between volcanological and hydroponic parameters. Componentry of the grades and pumice clast morphology, texture, density, and porosity were characterised. Vertical variations in the Rotorua and Taupō tephra profiles reflect changes in the eruption plume, degassing and/or conduit processes during the eruption. Settling velocities are reflected in lateral changes in pumice clast shape, size, and density in the Kaharoa deposits. The hydroponic parameters water holding capacity (WHC), bulk density and total porosity were found to be closely related to clast density and porosity and generally fall within the range of the tested hydroponic media. However, tephra WHC was generally lower than that of the hydroponic media. The low bulk density of the tephras particularly the 4-8 mm grade make them a relatively light material, however, their low WHC may limit their usefulness as a growing medium or require more frequent or alternate methods of irrigation. The higher bulk density and WHC of the 1-4 mm grade means it is likely to be better suited for many species.
Figures have been used without permission. Copyright holders may use the Copyright Take Down Request link below to request their removal.
Keywords: 370512 Volcanology